Kebijakan Formulasi Ketentuan Pengembalian Aset Hasil Tindak Pidana Korupsi - Kusnadi Kusnadi (Corruptio, 2020)
Law enforcement officials in settling cases of corruption do not only prioritize physical punishment, but also prioritize the recovery of state financial losses through the return of assets, therefore a system is needed that allows for the confiscation and seizure of assets resulting from corrupt acts effectively and efficiently. Policy on the Formulation of Provisions for Returning Assets resulting from Corruption in Indonesia is currently scattered in several laws including the Criminal Code, the Criminal Procedure Code, the Corruption Eradication Act (PTPK Law), the Law on Money Laundering (UU TPPU) and the United Nations Convention against Corruption  UNCAC) 2003. Formulation of provisions for returning assets in the future can apply the concept of confiscation of assets resulting from corruption without criminal penalties in accordance with Article 54 paragraph (1) letter c of UNCAC 2003. The research approach uses a normative juridical approach and an empirical juridical approach. The speakers consisted of prosecutors in the Indonesian Attorney General's Office, as well as Lecturers in Criminal Law at the Faculty of Law, University Lampung. Data collection was carried out with literature and field studies. Data analysis was performed qualitatively and then conclusions were drawn.  The results of the study show that the formulation of the provisions for returning assets as a result of corruption acts currently adheres to the concept of appropriation of assets through a court decision that has permanent legal force while the formulation of the provisions for returning assets as a result of corruption in the future is realized taking into account the interests of the State or the community as victims  from criminal acts of corruption by applying the Dutch concept of recovery of assets after a court decision, based on the concept of appropriation of assets against profits derived from the results of criminal acts, as well as applying the concept of appropriation of assets in a civil manner without being preceded by criminal sanctions as formulated in Article 1 paragraph (3) of the Draft Bill Confiscation of Criminal Asset.  Suggestions in this study should be the Government and the Parliament to harmonize the provisions of asset recovery contained in the PTPK Law and the TPPU Law to be in line with the concept of asset recovery (Asset Recovery) regulated in UNCAC 2003, to apply the concept of asset return after a court decision and the concept of appropriation of assets against profits. Obtained from the results of a criminal offense against amendments to the PTPK Law, and immediately ratified the Criminal Asset Seizure Draft Bill into Laws for effective return of assets resulting from a criminal act of corruption.